Synthesis of Buta-1,3-dienes through Palladium-Catalyzed Homocoupling of Aromatic Alkenes - Wen, Yanmei; Xie, Jianying; Deng, Chunmei; Wu, Yulian (Synlett, 2015)
A series of buta-1,3-dienes have been directly synthesized via a convenient palladium-catalyzed homodehydrogenation coupling reaction of aromatic alkenes under mild conditions. The homocoupling reaction enables a rapid synthesis of multisubstituted butadiene which shows typical aggregation-induced emission enhancement (AIEE) characteristics because it is practically not emissive in solution but emits blue fluorescence in aggregates.
Keywords: buta-1,3-dienes; dehydrogenative coupling; aggregation-induced emission; blue fluorescence